2020
DOI: 10.3390/jmse8020121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Top Tension on Vortex-Induced Vibration of Deep-Sea Risers

Abstract: With the increase of water depth, the design and use of the top-tensioned risers (TTR) are facing more and more challenges. This research presents the effect of top tension on dynamic behavior of deep-sea risers by means of numerical simulations and experiments. First, the governing equation of vortex-induced vibration (VIV) of TTR based on Euler-Bernoulli theory and Van der Pol wake-oscillator model was established, and the effect of top tension on natural vibration of TTR was discussed. Then, the dynamic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…According to previous studies [39][40][41], a parametric resonance often occurs at the low-order frequency of the structure. Therefore, in order to analyse the dynamics of the coupled system, the vibration of the first order modes for the riser and wake oscillator are investigated as follows.…”
Section: Galerkin Projection Of the Coupled Systemmentioning
confidence: 95%
See 1 more Smart Citation
“…According to previous studies [39][40][41], a parametric resonance often occurs at the low-order frequency of the structure. Therefore, in order to analyse the dynamics of the coupled system, the vibration of the first order modes for the riser and wake oscillator are investigated as follows.…”
Section: Galerkin Projection Of the Coupled Systemmentioning
confidence: 95%
“…With the development of technologies, impacts of the parametric excitation on the vibration of risers attract more and more attention as shown by the conducted experimental and numerical studies. The effect of top tension on dynamic behaviour of deep-sea risers was investigated numerically and experimentally by Zhang et al [41], and results showed that the vibration displacement for TTR increases and the bending stress decreases as the top tension increases. The experiment of VIV for a vertical variable-tension riser was conducted by Li et al [42], and it was shown that the dominant frequencies of risers in IL and CF directions, decrease gradually as the top tension is increased for a fixed flow velocity.…”
Section: Introductionmentioning
confidence: 99%
“…e design of the current velocity and the platform heave frequency in experiment is referred to the natural frequency of the TTR model (T �100 N). After the comparison between numerical simulations and experiments, it is proved that the calculating program is reliable [23].…”
Section: Test Introductionmentioning
confidence: 95%
“…e static component of the tension comes from the pretension imposed by the heave e dynamic component of the tension is caused by the heaving platform, and (Ω,a) is generally referred to as parametric excitations for the transverse vibration of TTR [21,22]. erefore, equation ( 1) is a partial differential equation with periodic variable coefficient, and this is different from the partial differential equation with constant variable coefficient in [23].…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation